Review: E. Carbé. 2023. Digitale d’autore. Macchine, archivi, letterature. Firenze: Firenze University Press; Siena: USiena Press. - Sartor, Marco (Umanistica Digitale, 2023)
How to foster the preservation and study of a born-digital literary archive? In the three chapters that comprise Digitale d’autore. Macchine, archivi, letterature the question is tackled from multiple points of view. In the first, after defining the object of investigation, Emmanuela Carbé outlines the historical, theoretical, and methodological aspects, including a definition of the relationship between writers and computers. This gives way in the central part of the volume to a review of the main experiences on both the national and international stage. Finally, the last section is dedicated to the critical framing of a work by investigating the born-digital archive conferred by the author to the institution in charge of its preservation.